Chylomicronemia mutations yield new insights into interactions between lipoprotein lipase and GPIHBP1 - Gin, Peter (Oxford University Press, 2012)
Lipoprotein lipase (LPL) is a 448-amino-acid head-to-tail dimeric enzyme that hydrolyzes triglycerides within capillaries. LPL is secreted by parenchymal cells into the interstitial spaces; it then binds to GPIHBP1 (glycosylphosphatidylinositol-anchored high density lipoprotein-binding protein 1) on the basolateral face of endothelial cells and is transported to the capillary lumen. A pair of amino acid substitutions, C418Y and E421K, abolish LPL binding to GPIHBP1, suggesting that the C-terminal portion of LPL is important for GPIHBP1 binding. However, a role for LPL's N terminus has not been excluded, and published evidence has suggested that only full-length homodimers are capable of binding GPIHBP1. Here, we show that LPL's C-terminal domain is sufficient for GPIHBP1 binding. We found, serendipitously, that two LPL missense mutations, G409R and E410V, render LPL susceptible to cleavage at residue 297 (a known furin cleavage site). The C terminus of these mutants (residues 298–448), bound to GPIHBP1 avidly, independent of the N-terminal fragment. We also generated an LPL construct with an in-frame deletion of the N-terminal catalytic domain (residues 50–289); this mutant was secreted but also was cleaved at residue 297. Once again, the C-terminal domain (residues 298–448) bound GPIHBP1 avidly. The binding of the C-terminal fragment to GPIHBP1 was eliminated by C418Y or E421K mutations. After exposure to denaturing conditions, the C-terminal fragment of LPL refolds and binds GPIHBP1 avidly. Thus, the binding of LPL to GPIHBP1 requires only the C-terminal portion of LPL and does not depend on full-length LPL homodimers.